Differential Effects of Temperature and Mosquito Genetics Determine Transmissibility of Arboviruses by Aedes aegypti in Argentina - Ciota, Alexander T. (2018)
Aedes aegypti (L.) (Diptera: Culicidae) have a global distribution and are the primary vector of a number of mosquito-borne viruses responsible for epidemics throughout the Americas. As in much of South America, the threat from pathogens including dengue virus (DENV; Flaviviridae, Flavivirus) and chikungunya virus (CHIKV; Togaviridae, Alphavirus) has increased in Argentina in recent years. The complexity of transmission cycles makes predicting the occurrence and intensity of arbovirus outbreaks difficult. To gain a better understanding of the risk of DENV and CHIKV in Argentina and the factors influencing this risk, we evaluated the role of population and temperature in the vector competence and vectorial capacity (VC) of Ae. aegypti from geographically and ecologically distinct locations. Our results demonstrate that intrinsic and extrinsic factors including mosquito population, viral species, and temperature significantly influence both vector competence and overall VC of Ae. aegypti in Argentina, yet also that the magnitude of these influences is highly variable. Specifically, results suggest that CHIKV competence is more dependent on mosquito genetics than is DENV competence, whereas temperature has a greater effect on DENV transmission. In addition, although there is an overall positive correlation between temperature and competence for both viruses, there are exceptions to this for individual virus?population combinations. Together, these data establish large variability in VC for these pathogens among distinct Ae. aegypti populations in Argentina and demonstrate that accurate assessment of arbovirus risk will require nuanced models that fully consider the complexity of interactions between virus, temperature, mosquito genetics, and hosts.